KEPUASAN KONSUMEN PADA MENU BEST SELLER (NASI GORENG PANGERAN) DI RESTORAN HOTEL PANGERAN BEACH PADANG - Putri, Saima; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine Costumer Satisfaction with the Best Seller Menu (Nasi Goreng Pangeran) at the Pangeran Beach Hotel Padang, including 5 sub-variables (1) Product Quality, (2) Service Quality, (3) Emotional Factors, (4) Price, (5) Cost. This research uses quantitative methods using a Likert scale and the data collection techniques used are observation, questionnaires and documentation. The research population was guests who visited and ordered the Nasi Goreng Pangeran menu at the Hotel Pangeran Beach Padang restaurant and the research sample size was 100 people. Based on the research results, it can be concluded that consumers who order and eat Prince fried rice at the Pangeran Beach Padang Hotel restaurant can be said to be very satisfied with a total score of 7341 where the overall score range of 7150-8800 falls into the "Very Satisfied" category. (can be seen in table 4.11 of the results of the recapitulation of respondents' responses). From these results it can also be interpreted that the Hotel Pangeran Beach Padang restaurant has met consumer expectations regarding the Pangeran Fried Rice menu. For the Pangeran Beach Padang Hotel restaurant to be able to maintain and increase results, we are very satisfied with the quality of the products and the quality of service, especially on the best-selling menu. And for the price of Prince's fried rice which has the lowest score, it would be better if Hotel Pangeran Beach Padang could reconsider the price offered for this menu, or could increase the quality of Prince's fried rice so that it is comparable to the price offered. And for the Head of Department to be able to hold training for all employees in the restaurant to improve the quality of service provided to guests because that is the key to the hospitality industry. Keywords: Customer Satisfaction, Best Seller, Menu, Restaurant